Study on optimum condition in ph solution of rice husk based superabsorbent polymer composite - Nurul Akma, Reduan (2013)
Poly Rice Husk-Acrylic acid-co-Acrylamide superabsorbent polymer composite (RH-AA-AM SAPC) was synthesized by solution polymerization of the Acrylic Acid (AA) and Acrylamide (AM) monomer onto RH fibre using Ammonium Persulphate (APS) and N, N- methylene bisacrylamide (MBA) which act as an initiator and crosslinker, respectively. The optimal conditions for synthesizing the polymer with the highest water absorbency have been identified by studying the water absorption of the polymer with the effect of initiator, crosslinking agent and filler amounts. Maximum water absorbency of RH-AA-AM SAPC was achieved at 10 wt% on initiator, 0 wt% of crosslinking agent and 10 wt% of filler amount which results on 115.5155 gIg, 91.4020 gIg, and 44.7940 g/g water absorbency. Finally, the optimum water absorbency in pH solution was observed at pH 4 for all parameters varies. The samples were characterized by using Fourier Transform Infrared (FTIR) analysis, Thermogravimetric Analysis (TGA) and Field Emission Spectroscopy Electron Microscopy (FESEM). The TGA analysis shown that thermal stability of RH-AA-AM SAPC was better than Pure SAP, meanwhile FTIR analysis shown RR-SAPC have sharp peak of bonding curve shape to Pure SAP.